2020
DOI: 10.1186/s40854-019-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Tail dependence in emerging ASEAN-6 equity markets: empirical evidence from quantitative approaches

Abstract: This study contributes a rich set of quantitative methodologies including a nonparametric approach (Chi-plots and K-plots) as well as copulas (traditional and timevarying with Student's t-copulas) to the existing literature in terms of determining the dependence structure in ASEAN stock markets. Drawing on the emerging ASEAN equity returns of six countries from January 2001 to December 2017, we found that Student's t-copulas under time-varying approach is the most appropriate approach to explain these co-movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…(2014) found stock market volatility in Indonesia, the Philippines and Thailand was related and had a tail dependence. These results were consistent with those of Duong and Huynh (2020), who found the left- and right-tail dependence on the volatility of stock markets in Vietnam, Thailand, Singapore, the Philippines, Malaysia and Indonesia. Pongkongkaew et al.…”
Section: Literature Reviewsupporting
confidence: 92%
See 1 more Smart Citation
“…(2014) found stock market volatility in Indonesia, the Philippines and Thailand was related and had a tail dependence. These results were consistent with those of Duong and Huynh (2020), who found the left- and right-tail dependence on the volatility of stock markets in Vietnam, Thailand, Singapore, the Philippines, Malaysia and Indonesia. Pongkongkaew et al.…”
Section: Literature Reviewsupporting
confidence: 92%
“…Studies undertaken before the COVID-19 pandemic revealed the existence of previous volatility in ASEAN stock markets. Stock markets in the ASEAN Economic Community (AEC) have also been found to have relationships with each other and other stock markets outside the region (Click and Plummer, 2005;Janor and Ali, 2007;Sriboonchitta et al, 2014;Duong and Huynh, 2020;Chitkasame and Tansuchat, 2019;Pongkongkaew et al, 2020;Lim, 2007;Jakpar et al, 2013;Lean and Smyth, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…ARCH models do not use the past standard deviations but formulate conditional variance with maximum likelihood procedure. GARCH model (Benzid and Chebb 2020 ) that also allows for asymmetrical dependencies includes the GJR-GARCH proposed by Glosten et al ( 1993 ) and application of GJR-GARCH model in the ASEAN (Association of Southeast Asian Nations) market well documented by Nguyen and Huynh ( 2019 ) and Duong and Huynh ( 2020 ). In order to regard information of asymmetry of the DONs, we model the energy market volatility using the GJR-GARCH (1,1) model as follows:…”
Section: Empirical Model and Hypothesis Developmentmentioning
confidence: 99%
“…Some researchers have also used the time-varying copula model to study a particular financial market. Duong and Huynh [21] and Wu et al [22] studied the risk in the stock market. e latter focused on the impact of RMB exchange rate and equity spillover effects and found a positive relationship between them.…”
Section: Literature Reviewmentioning
confidence: 99%